2015
DOI: 10.1016/j.toxrep.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Sub-chronic exposure to fipronil induced oxidative stress, biochemical and histopathological changes in the liver and kidney of male albino rats

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
70
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 47 publications
(79 reference statements)
13
70
0
2
Order By: Relevance
“…All these findings lead to the conclusion that the oxidative stress due to metribuzin may be ascribed to the induction of ROS production as evidenced by increased LPO levels, resulting in the depletion of GSH contents that could be the cause of decreased activity of GPx. These results were in line with previous studies which have shown that exposure to pesticide generates lipid peroxidation and alters the antioxidant status of several tissues in rats [38,40,41].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…All these findings lead to the conclusion that the oxidative stress due to metribuzin may be ascribed to the induction of ROS production as evidenced by increased LPO levels, resulting in the depletion of GSH contents that could be the cause of decreased activity of GPx. These results were in line with previous studies which have shown that exposure to pesticide generates lipid peroxidation and alters the antioxidant status of several tissues in rats [38,40,41].…”
Section: Discussionsupporting
confidence: 93%
“…Lipid peroxidation is a chemical mechanism capable of disrupting the structure and the function of the biological membranes that occurs as a result of free radical attack on lipids which was usually reflected by levels of MDA [37]. Therefore, it has used as biomarkers of pesticides induced oxidative stress and suggested as one of the molecular mechanisms involved in pesticides-induced toxicity [38].…”
Section: Discussionmentioning
confidence: 99%
“…NAPQI leads to the oxidation of macromolecules such as lipids or SH group of proteins. In our study, we found that multiple doses of paracetamol produced a many fold marked elevation of the serum levels of ALT, ALP AST and LDH 95.50 ± 4.20 IU/L89.15 ± 2.36 IU/L, 90.12 ± 2.12 IU/L and 190.12 ± 4.20 IU/L respectively in animals when compared with that of the control group AST, ALT, ALP and LDH levels 43.25 ± 1.95, 30.10 ± 2.55, 40.12 ± 2.45 and 95.12 ± 3.50 confirming altered liver function and changes in the structural integrity of hepatic cells [32].A substantial upsurge in the direct, as well as indirect bilirubin levels to 2.415 ± 0.445 mg/dl and 0.489 ± 0.002 mg/dL in paracetamol-treated animals, respectively was detected. Studies have demonstrated that paracetamol-induced hepatotoxicity can be amended by substance that influence the activity of cytochrome P450 activity [33].The natural antioxidants present in many plants due to their free radical scavenging activities reduce oxidative damage and boost the antioxidant defense system enzymes [34].In our study, we demonstrate that the methanolic extract of Elsholtzia densa decreased the levels of AST(51.12 ± 2.20), ALT (49.15 ± 3.25), ALP (44.12 ± 2.56) and LDH (125.15 ± 4.45) at higher dose of the extract (300 mg/kg) which were statistically significant with respect to the positive controls (▶table 3) indicating that the extract was effective in safeguarding the structural integrity of the liver from the hostile effects of paracetamol hepatotoxicity.…”
Section: Discussionmentioning
confidence: 64%
“…Hematoxylin stains the nuclei within cells blue and eosin stains the cytoplasm of cells pink. Results from histopathology tests help to clarify in combination with genotoxicity tests, the adverse effects from the exposure of chemical substances, such as pesticides, and their potential impact as shown in various studies (Abdel-Tawab et al, 2015, Marx-Stoelting et al, 2015, Tsitsimpikou et al, 2013, Zafiropoulos et al, 2014. The possible toxic outcome when one or more chemical substances are applied together is the result of agent-to-agent interactions, toxicodynamic and toxicokinetic interactions.…”
Section: Introductionmentioning
confidence: 99%